Flexible beam delivery of ultrafast laser through vacuum-pumped anti-resonant hollow-core fiber - Cai, Yiming; Mai, Yifan; Xiang, Shen; Shi, Jianhong; Zhu, Qixin; Li, Rong; Li, Jinyan; Li, Cheng; Yan, Dapeng; Xing, Yingbin (Frontiers in Physics, 2023)
We demonstrate the transmission of a 100 MW-peak-power ultrafast laser through a 5-m anti-resonant hollow-core fiber (AR-HCF) with a pumpable armored tube for air exhaust. The AR-HCF consists of a 45-μm-hollow-core and seven untouched capillaries with an attenuation of 0.11 dB/m measured at a wavelength of 1030 nm. We investigate the effect of air-filling and vacuum pumping on transmission efficiency and pulse distortion. The comparison reveals the importance of controlling air concentration in hollow-core fibers (HCFs) for achieving high transmission efficiency and pulse quality. With the suppression of air concentration, the transmission efficiency increases from 61% to 72%, and pulse distortion is effectively controlled. The results demonstrate the potential of AR-HCFs for high-power ultrafast laser delivery systems for various applications. The pumpable armored tube design provides a simple and effective solution to suppress self-phase modulation (SPM) and enable flexible beam delivery.